Association between passively collected walking and bicycling data and purposefully collected active commuting survey data—United States, 2019. (May 2023) - Soto, Graycie W.; Webber, Bryant J.; Fletcher, Kelly; Chen, Tiffany J.; Garber, Michael D.; Smith, Akimi; Wilt, Grete; Conn, Michel; Whitfield, Geoffrey P.
Abstract: Commercially-available location-based services (LBS) data derived primarily from mobile devices may provide an alternative to surveys for monitoring physically-active transportation. Using Spearman correlation, we compared county-level metrics of walking and bicycling from StreetLight with metrics of physically-active commuting among U.S. workers from the American Community Survey. Our strongest pair of metrics ranked counties (n = 298) similarly for walking (rho = 0.53 [95% CI: 0.44–0.61]) and bicycling (rho = 0.61 [0.53–0.67]). Correlations were higher for denser and more urban counties. LBS data may offer public health and transportation professionals timely information on walking and bicycling behavior at finer geographic scales than some existing surveys. Highlights: Active transportation data from mobile devices may have public health applications. We compared data from StreetLight Inc. and the American Community Survey (ACS). Most correlations between the StreetLight and ACS metrics were strong or moderate. Correlations were higher for denser and more urban counties. Population mobility data may enhance surveillance of walking and bicycling behavior.